Pengembangan Energi Terbarukan Biomassa dari Sumber Pertanian, Perkebunan dan Hasil Hutan: Kajian Pengembangan dan Kendalanya - Kasmaniar Kasmaniar; Syaifuddin Yana; Nelly Nelly; Fitriliana Fitriliana; Susanti Susanti; Filia Hanum; Aidil Rahmatullah (Jurnal Serambi Engineering, 2023)
Many developing nations, including Indonesia, depend on energy for socioeconomic growth. However, the government must control sustainable biomass exploitation, use, and development. Increasing biomass use for many purposes. Indonesia has 49,810 MW of plant-based biomass. Over the past decade, Indonesia's energy demand has grown 7%. This study examines barriers to renewable energy from agricultural, plantation, and forest biomass. Developer-producer integration in energy production is a challenge. Misuse of raw material sources, especially in supply chains, can destabilize forest biomass sources in the future. Due to insufficient education, farm workers lack experience and information about correct processing. Farmers employ traditional implements. This substantially limits agricultural waste conversion into renewable energy. Another issue: biomass resource overlap. Regulating sectors, agencies, ministries, and producers is crucial. This governs linked institutions (between regions, agencies, ministries both in the utilization and regulation of their interests).